Pengembangan Kemampuan Kreativitas dalam Pembelajaran IPS - Fadillah, Allya; Amini, Amini; Sahfitri, Anggi Ayu; Lubis, Kamalia; Mahyuni, Lela; Abdi, Khoirul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The field application shows that social science education is still mainly theoretical. The attitude that social science education is only